2006
DOI: 10.1055/s-2006-924723
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early Onset Multiple Sclerosis with Suboptimal Dose of Interferon Beta-1a

Abstract: Treatment with interferon beta-1a is well tolerated for a long period of time and may be effective in substandard doses in early onset multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 10 publications
0
29
0
1
Order By: Relevance
“…24,26 In one unblinded study, 16 patients were randomized to intramuscular IFN-b-1a, half of adult dose, once a week or to no treatment. After 4 years, relapse rates (p 5 0.04), disability progression (p 5 0.01), and new T2 lesions (p 5 0.006) were lower in treated vs untreated patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24,26 In one unblinded study, 16 patients were randomized to intramuscular IFN-b-1a, half of adult dose, once a week or to no treatment. After 4 years, relapse rates (p 5 0.04), disability progression (p 5 0.01), and new T2 lesions (p 5 0.006) were lower in treated vs untreated patients.…”
mentioning
confidence: 99%
“…After 4 years, relapse rates (p 5 0.04), disability progression (p 5 0.01), and new T2 lesions (p 5 0.006) were lower in treated vs untreated patients. 26 In another study, controls were extracted from a database: after a mean follow-up of 5.5 years, patients treated with IFN-b demonstrated significantly reduced occurrence of relapses, especially in the first 2 years of exposure, and a decrease in development of severe disability, although not statistically significant 24 (table 1). Most studies have demonstrated a favorable effect of IFN-b on pediatric MS evolution, with a decline of relapse rate during the treatment phase, compared to the pretreatment period.…”
mentioning
confidence: 99%
“…Randomized controlled trials in pediatric MS have been very rare (Unkel et al., ), but are becomming more common now (Rose & Müller, ). We consider a randomized controlled trial assessing efficacy and safety of interferon beta‐1a compared to no treatment in pediatric MS reported by Pakdaman, Fallah, Sahraian, Pakdaman, and Meysamie (). In this trial, 16 patients were randomized to verum or control.…”
Section: Two Illustrative Examplesmentioning
confidence: 99%
“…These injectable therapies have been shown to be effective in reducing the relapse rate with a generally favorable safety profile by several observational studies [49][50][51][52] and some unblinded RCT. 53,54 In general, it is recommended to initiate interferon-beta at one-quarter of the adult-dose and increase slowly up to the full adult dose, especially for children aged 12 years and older with a bodyweight more than 30 kg. 46 As for glatiramer acetate, it can be initiated at the full adult dose.…”
Section: Treatment Of Pediatric Msmentioning
confidence: 99%